Human Nature An Interdisciplinary Biosocial Perspective - Calistro Alvarado, Louis; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Human Nature is dedicated to advancing the interdisciplinary investigation of the biological, social, and environmental factors that underlie human behavior. It focuses primarily on the functional unity in which these factors are continuously and mutually interactive. These include the evolutionary, biological, and sociological processes as they interact with human social behavior; the biological and demographic consequences of human history; the cross-cultural, cross-species, and historical perspectives on human behavior; and the relevance of a biosocial perspective to scientific, social, and policy issues.
Keywords: Behavioral sciences; Anthropology; Biological psychology; Anthropology; Behavioral Sciences; Biological Psychology